2011
DOI: 10.4103/1450-1147.89780
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Considerations in Radioimmunotherapy and Systemic Radionuclide Therapies: A Review

Abstract: Radiopharmaceutical therapy, once touted as the “magic bullet” in radiation oncology, is increasingly being used in the treatment of a variety of malignancies; albeit in later disease stages. With ever-increasing public and medical awareness of radiation effects, radiation dosimetry is becoming more important. Dosimetry allows administration of the maximum tolerated radiation dose to the tumor/organ to be treated but limiting radiation to critical organs. Traditional tumor dosimetry involved acquiring prethera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Some favorable arguments include: i) radioiodinated Hyp can selectively and intensively be distributed in necrosis at concentrations as high as 4-10 %ID/g (19,29); ii) radioiodinated Hyp presents a biological half-life (Tb 1/2 ) of two days allowing high levels of accumulation in the tumor site before being eliminated from the body; and iii) the relatively long physical half-life of 8.06 days with beta-emitting 131 I fits well with the prolonged retention of 131 I-Hyp at intratumoral necrosis, which may synergistically create a hostile microenvironment sterilizing the residual cancer cells (16,19,29,30). Indeed, the current study has demonstrated that 131 I-Hyp consequently delivered the radiation doses as high as 276-93,600 mGy/MBq to necrotic tissues, and such emitted beta particles with a maximum energy of 606 keV can penetrate through the tissue up to a distance of 0.6-2.0 mm from the resident site (31). Eventually, the nearby cancer cells may be reached, irradiated and killed by the beta radiation associated tumoricidal effect via DNA damage and apoptotic activation (32).…”
Section: Discussionmentioning
confidence: 62%
“…Some favorable arguments include: i) radioiodinated Hyp can selectively and intensively be distributed in necrosis at concentrations as high as 4-10 %ID/g (19,29); ii) radioiodinated Hyp presents a biological half-life (Tb 1/2 ) of two days allowing high levels of accumulation in the tumor site before being eliminated from the body; and iii) the relatively long physical half-life of 8.06 days with beta-emitting 131 I fits well with the prolonged retention of 131 I-Hyp at intratumoral necrosis, which may synergistically create a hostile microenvironment sterilizing the residual cancer cells (16,19,29,30). Indeed, the current study has demonstrated that 131 I-Hyp consequently delivered the radiation doses as high as 276-93,600 mGy/MBq to necrotic tissues, and such emitted beta particles with a maximum energy of 606 keV can penetrate through the tissue up to a distance of 0.6-2.0 mm from the resident site (31). Eventually, the nearby cancer cells may be reached, irradiated and killed by the beta radiation associated tumoricidal effect via DNA damage and apoptotic activation (32).…”
Section: Discussionmentioning
confidence: 62%
“…These findings suggest that the 90 Y-labeled antibodies have the potential to deliver a lethal dose of radiotherapy to c-kit-expressing SCLC. The dose-limiting organ for RIT with IgG is commonly the red marrow, and consideration of the absorbed dose to the red marrow is important in determining the therapeutic radiation dose in patients [33]. In the present study, the absorbed dose estimated from our biodistribution data was 0.5 mGy/MBq in a 70-kg reference man for both 90 Y-labeled antibodies;≤2 Gy is commonly considered to be a safe radiation dose [33], indicating that the estimated maximum therapeutic dose is 4 GBq.…”
Section: Discussionmentioning
confidence: 99%
“…Mice received up to 2 injections of 22.2 MBq (0.6 mCi), with no observable side effects, which would scale up to 62 GBq (1,680 mCi) per injection in humans. The red marrow would be the dose-limiting organ for radioimmunotherapy studies, because it is well known that the maximum tolerated dose in this organ is reached at a lower absorbed dose than other organs (39). On the basis of the dosimetry data presented here, the estimated dose to the red marrow would be 2,860 mSv (286 rad), which is in the range of 3,000 mSv (300 rad) to the marrow that has been shown to induce a 1% chance of leukemia within 10 y after exposure.…”
Section: Discussionmentioning
confidence: 99%